2021
DOI: 10.1038/s41598-021-88435-w
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of binocular vision after alcohol intake influences driving performance

Abstract: In this study, we assessed the influence of moderate alcohol intake on binocular vision, vergence system and simulated driving performance by analyzing the interactions between visual deterioration and driving variables. Thirty young healthy subjects were recruited. For the analysis, we measured: visual function (visual acuity and stereoacuity), phorias and fusional reserves. Also, we checked Sheard’s and Percival’s criteria at near and far. The accommodative convergence/accommodation (AC/A) ratio was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 74 publications
4
8
0
Order By: Relevance
“…Finally, in line with the OIDS calculation and other studies, 18,36,57,63 an overall binocular summation score (OBSS) was also calculated for the visual functions analysed (VA, CSF and VDI), and for all of the filter conditions. To do this, we averaged the z ‐scores of these visual function variables for each filter condition.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, in line with the OIDS calculation and other studies, 18,36,57,63 an overall binocular summation score (OBSS) was also calculated for the visual functions analysed (VA, CSF and VDI), and for all of the filter conditions. To do this, we averaged the z ‐scores of these visual function variables for each filter condition.…”
Section: Methodsmentioning
confidence: 99%
“…For all the variables, the more positive the score, the greater the interocular differences. Z-scores have been widely used 18,36,57,63 and are a measurement of how many standard deviations an individual value lies away from the group mean.…”
Section: Interocular Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, some works have shown that exophoria (increased at near vision tasks under the effects of alcohol) has a lesser effect on stereopsis, although it may vary depending on the magnitude of the exophoria [ 10 , 11 ]. However, esophoria (increased at distance) has a greater influence [ 8 , 12 , 13 ]. The effects of alcohol consumption on other visual functions, such as halo perception (and other night vision dysphotopsia) and objective measurements (such as the retinal image quality) have been less studied.…”
Section: Introductionmentioning
confidence: 99%